(Re)Assessing contemporary "fear of crime" measures within an Australian context. (September 2016) - Chataway, Michael L.; Hart, Timothy C.
Abstract: Data collected from residents living in southeast Queensland, Australia ( N = 713) are used to replicate a prior evaluation of multiple indicators of "fear of crime." Results of confirmatory factor analysis (CFA) and structural equation modeling (SEM) support evidence produced from a UK survey that indicators of worry, belief, control, likelihood, and consequences of victimisation demonstrate good scaling properties. Furthermore, current findings suggest that these constructs are theoretically distinct. Finally, residents' perceptions of the neighbourhoods in which they live are believed to affect attitudes about crime and are consistent with social-psychological models of crime fear. Current findings are discussed in terms of their implications on understanding fear of crime from both an academic and practitioner perspective. Highlights: The current study is a replication study of prior work testing a social-psychological model of fear of crime. A simple random sample of Australian residents was used. Resident's worry about personal and property victimisation was represented by five key dimensions of fear of crime. Perceptions of the physical environment predicted resident's worry about potential personal and property victimisation.